LANGUAGE FUNCTIONS USED BY SHAHNAZ HAQUE INTUPPERWARE SHE CANON TRANS 7 - PUTRI, AULIA NOURMA (Jurnal Ilmiah Mahasiswa FIB, 2013)
This study was conducted to find out the types of language functions and vocabulary choices used by Shahnaz Haque in hosting Tupperware She Can on Trans 7. The writer selected Tupperware She Can as the data source since it shares inspiring stories from Indonesian women to motivate others to contribute more in society. Furthermore, the writer took four steps in analyzing the data: grouping the utterances containing language function into a table, analyzing the data which contain language function, analyzing the text analysis focused on vocabulary choices and discussing and summarizing the findings. The results show that there are sixty utterances containing five out of seven types of language function: ideational-referential, ideational-metalingual, ideational-phatic, interpersonal-emotive and interpersonal-directive function. The writer also found thirteen vocabularies which have explicit meaning to deliver her message well. From the findings above, we can conclude that language function and the vocabulary choice is needed in communication because they are the point of the success of meaning delivery process.   Keywords : discourse analysis, language functions, vocabulary choice.